EDUCATION BASED ON NATIONAL VALUES IN PRESCHOOL EDUCATION (Global Economic Review: Journal of Economics, Policy, and Business Development, 2026)
The article studied and analyzed the upbringing of schoolchildren in the spirit of national values, the provision of scientific and theoretical knowledge on the basis of various didactic materials. The possibilities of foreign public preschool organizations were also described.